Clinical Efficacy Observation of Integrated Traditional Chinese and Western Medicine Therapy in the Treatment of Acne Vulgaris - Zhou, Qiang; Chen, Zhenlin (Journal of Contemporary Medical Practice, 2025)
Objective: To observe the clinical efficacy and safety of traditional Chinese medicine (TCM) decoction combined with clindamycin phosphate gel in the treatment of acne vulgaris. Methods: A total of 70 patients with acne vulgaris were randomly divided into an observation group (n=35) and a control group (n=35) following a randomized, controlled, single-blind design. The control group received topical clindamycin phosphate gel, while the observation group was additionally treated with oral TCM decoction. The treatment duration was 7 days per course, with a total of 28 days for both groups. Clinical efficacy and adverse reactions were recorded at 14 and 28 days of treatment. Results: After four treatment courses, the overall effective rate and cure rate in the observation group were significantly higher than those in the control group. Conclusion: The combination of TCM and Western medicine can further improve therapeutic outcomes in acne vulgaris and is worthy of clinical promotion.